2018
DOI: 10.12944/crnfsj.6.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Obesity Among Female School Teachers and its Associated Health Problems

Abstract: Obesity is considered to be a major health problem throughout the world. Factors contributing to obesity include increased intake of calorie dense foods and physical inactivity. Teachers represent one of the most important, large and growing sector of workforce in many countries. The objective of the present study was to determine risk of obesity among female school teachers along with various factors and health problems associated with it. A descriptive cum cross-sectional survey was conducted among 500 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(13 reference statements)
2
3
1
1
Order By: Relevance
“…The ndings from this study have also shown a signi cant difference in the prevalence of overweight and obesity between female teachers and their male counterparts, where female teachers were 43% more likely to be overweight or obese. The same observation was reported by other studies from Tanzania 24,26 , Ghana 11 , Nigeria 18,21 , Malaysia 17 , South Africa 8,12,20 and India 16 . This may be explained partly by the nature of female's anatomy.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The ndings from this study have also shown a signi cant difference in the prevalence of overweight and obesity between female teachers and their male counterparts, where female teachers were 43% more likely to be overweight or obese. The same observation was reported by other studies from Tanzania 24,26 , Ghana 11 , Nigeria 18,21 , Malaysia 17 , South Africa 8,12,20 and India 16 . This may be explained partly by the nature of female's anatomy.…”
Section: Discussionsupporting
confidence: 89%
“…The high prevalence of overweight or obesity among primary and secondary school teachers found in this study (72.7%), was comparable to other studies conducted among teachers, where it was 74.3% in Malaysia 17 , 70% in India 16 , and 85% in Cape Town, South Africa 8 . The observed similarities in all these studies may be explained partially by the fact that they were all conducted in urban populations and that they all recruited mainly female participants.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Teachers as a professional group have been shown to experience many risk factors that may predispose them to developing both obesity and hypertension [11]. Teaching is a mentally stressful occupation.…”
Section: Check For Updatesmentioning
confidence: 99%